Construction of an infectious cDNA clone of Enterovirus 71: Insights into the factors ensuring experimental success - Lazouskaya, Natallia V. (J Virol Methods, 2014)
Enterovirus 71 (EV 71) is a causative agent of mild Hand Foot and Mouth Disease but is capable of causing severe complications in the CNS in young children. Reverse genetics technology is currently widely used to study the pathogenesis of the virus. The aim of this work was to determine and evaluate the factors which can contribute to infectivity of EV 71 RNA transcripts in vitro. Two strategies, overlapping RT-PCR and long distance RT-PCR, were employed to obtain the full-length genome cDNA clones of the virus. The length of the poly(A) tail and the presence of non-viral 3′-terminal sequences were studied in regard to their effects on infectivity of the in vitro RNA transcripts of EV 71 in cell culture. The data revealed that only cDNA clones obtained after long distance RT-PCR were infectious. No differences were observed in virus titres after transfection with in vitro RNA harbouring a poly(A) tail of 18 or 30 adenines in length, irrespective of the non-viral sequences at the 3′-terminus.